2013
DOI: 10.7314/apjcp.2013.14.12.7207
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated with Mammography Adherence among Married Chinese Women in Yanbian, China

Abstract: Background: Despite the efficacy of regular mammograms, the incidence and mortality rate of breast cancer have been increasing in China. Insufficient studies on the factors affecting mammography adherence in Chinese married women have been conducted. The purpose of the present study was to explore the factors associated with adherence to guidelines for regular mammography among Chinese married women. Materials and Methods: The participants were recruited conveniently and included Chinese and Korean Chinese wom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
12
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 34 publications
2
12
1
Order By: Relevance
“…Based on these findings, miR-181a-5p was supposed to be a tumour suppressor. In contrast, a number of studies showed that miR-181a-5p was upregulated and acted as an oncomiR in gastric carcinogenesis by suppressing RASSF6, ATM or KLF6 expression [29, 4345]. In accordance with these findings, we showed that miR-181a-5p promoted proliferation and migration of GC cells and enhanced tumour growth in vivo.…”
Section: Discussionsupporting
confidence: 85%
“…Based on these findings, miR-181a-5p was supposed to be a tumour suppressor. In contrast, a number of studies showed that miR-181a-5p was upregulated and acted as an oncomiR in gastric carcinogenesis by suppressing RASSF6, ATM or KLF6 expression [29, 4345]. In accordance with these findings, we showed that miR-181a-5p promoted proliferation and migration of GC cells and enhanced tumour growth in vivo.…”
Section: Discussionsupporting
confidence: 85%
“…This was slightly lower than the 44.7% -48.2% of the age from forties to sixties women undergoing mammography within 2 years, reported from a nation-wide survey (KBCS, 2013). However, this was higher than the 24% reported from a study of Chinese and Korean Chinese women who are married (Gang et al, 2013).…”
Section: Discussioncontrasting
confidence: 64%
“…Among full time employees, time flexibility may be an important factor to induce high job stress and a barrier to obtaining a health examination (Kim et al, 2009;Kim et al, 2011). It was reported that the women less than high school graduates has showed less regular mammography performance as 0.4 times (Gang et al, 2013). However this study showed no significant differences of regular mammography performance between education levels.…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…(Kochhar et al, 2013;Gang et al, 2013;Mohammadi et al, 2013;Boonlikit et al, 2013;Cabuk et al, 2014;Hu et al, 2014;Ozkan-Gurdal et al, 2014;El Sharkawi et al, 2014;Meiyanto et al, 2014;Avci et al, 2014;Fouladi et al, 2014;Alipour et al, 2014). We comprehensively reviewed risk factors for lymphedema among breast cancer survivors.…”
Section: Discussionmentioning
confidence: 99%